Multiparametric Flow Cytometry Using Near-Infrared Fluorescent Proteins Engineered from Bacterial Phytochromes - Telford, William G. (PLoS One, 2015)
Engineering of fluorescent proteins (FPs) has followed a trend of achieving longer fluorescence wavelengths, with the ultimate goal of producing proteins with both excitation and emission in the near-infrared (NIR) region of the spectrum. Flow cytometers are now almost universally equipped with red lasers, and can now be equipped with NIR lasers as well. Most red-shifted FPs of the GFP-like family are maximally excited by orange lasers (590 to 610 nm) not commonly found on cytometers. This has changed with the development of the iRFP series of NIR FPs from the protein family of bacterial phytochromes. The shortest wavelength variants of this series, iRFP670 and iRFP682 showed maximal excitation with visible red lasers. The longer wavelength variants iRFP702, iRFP713 and iRFP720 could be optimally excited by NIR lasers ranging from 685 to 730 nm. Pairs of iRFPs could be detected simultaneously by using red and NIR lasers. Moreover, a novel spectral cytometry technique, which relies on spectral deconvolution rather than optical filters, allowed spectra of all five iRFPs to be analyzed simultaneously with no spectral overlap. Together, the combination of iRFPs with the advanced flow cytometry will allow to first image tissues expressing iRFPs deep in live animals and then quantify individual cell intensities and sort out the distinct primary cell subpopulations ex vivo.